2018
DOI: 10.29271/jcpsp.2018.05.378
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Of Low Temperature With Testicular Torsion

Abstract: Acute testicular torsion was seen more commonly in cold season with low temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This result suggested us that seasons had no effect on the development of acute scrotum. It has been identified in a study that left testicle was more frequently torsioned (58%) (13). In also our study, TT was more frequently encountered in the left testicle in (75%) consistently with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…This result suggested us that seasons had no effect on the development of acute scrotum. It has been identified in a study that left testicle was more frequently torsioned (58%) (13). In also our study, TT was more frequently encountered in the left testicle in (75%) consistently with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…The study of Hoshino et al [18] found that over 75% of cases of TT occurred when the ambient temperature was below 15°C in Japan. Furthermore, Ekici et al [19] reported in their study that there were 14 (46.6%) cases of TT in the winter months, 7 (23.3%) in the spring months, 4 (13.3%) in the summer months, and 5 (16.6%) in the fall months. Acute TT in the winter was statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies reported that, worldwide, the delayed diagnosis and management of TT was quite common, and a relatively high proportion of TT patients proven to be delayed even in tertiary hospitals [ 7 , 8 ]. Aaron P. Bayne et al [ 1 ] and Christopher E. Bayne et al [ 9 ], in the United States, and Ekici et al [ 10 ] in Turkey, have investigated the clinical, socioeconomic and other factors associated with delayed management of TT, while there have no relevant reports among Chinese populations. Identifying the factors that cause delayed management of pediatric TT in China would help to establish targeted medical health-care plans, salvage affected testes, and eventually protect boys’ reproductive health.…”
Section: Introductionmentioning
confidence: 99%